Equitable Distribution of Nurses: a Concept Analysis Approach - Setiawan, Nugroho Budi; Ariati, Wiwik; Pranata, Satriya; Mubin, M. Fatkhul (Journal Research of Social Science, Economics, and Management, 2025)
The equitable distribution of nurses is a foundational element of health system equity and effectiveness. Disparities in nurse allocation between urban and rural areas have long been recognized as barriers to achieving universal health coverage and patient-centered care. Despite policy efforts, the concept of equity in nurse distribution often remains undefined and inconsistently applied in practice. This paper applies Walker and Avant’s (2010) concept analysis approach to clarify the meaning, attributes, antecedents, and consequences of equitable distribution of nurses as a central concept in nursing administration and workforce planning. Through theoretical analysis and synthesis of literature, five defining attributes were identified: fairness, accessibility, competence alignment, sustainability, and policy responsiveness. The findings highlight that equitable nurse distribution extends beyond numerical balance, reflecting ethical, structural, and reflective dimensions of the nursing discipline. This conceptual clarity contributes to a stronger theoretical framework for nursing management and supports evidence-based policymaking to ensure justice and quality in healthcare delivery.